2002
DOI: 10.1128/mmbr.66.3.407-425.2002
|View full text |Cite
|
Sign up to set email alerts
|

Human Telomerase and Its Regulation

Abstract: The telomere is a special functional complex at the end of linear eukaryotic chromosomes, consisting of tandem repeat DNA sequences and associated proteins. It is essential for maintaining the integrity and stability of linear eukaryotic genomes. Telomere length regulation and maintenance contribute to normal human cellular aging and human diseases. The synthesis of telomeres is mainly achieved by the cellular reverse transcriptase telomerase, an RNA-dependent DNA polymerase that adds telomeric DNA to telomere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
672
0
18

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 761 publications
(705 citation statements)
references
References 258 publications
(388 reference statements)
15
672
0
18
Order By: Relevance
“…The core of this enzyme from all species is minimally composed of a protein-catalytic subunit and a single-stranded RNA called TERT and TR, respectively (Nugent and Lundblad, 1998;Collins, 2006). The expression of TERT has been demonstrated as a rate-limiting step in human cellular telomerase activation, and it is suppressed by multiple tumor-suppressor pathways in normal human cells but is activated by numerous oncogenic transcription factors (Meyerson et al, 1997;Liu et al, 2000;Cong et al, 2002;Lin and Elledge, 2003;Goueli and Janknecht, 2004). After its expression, regulations of the subcellular transportation of the TERT protein contribute to telomere homeostasis maintenance in telomerase-positive cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…The core of this enzyme from all species is minimally composed of a protein-catalytic subunit and a single-stranded RNA called TERT and TR, respectively (Nugent and Lundblad, 1998;Collins, 2006). The expression of TERT has been demonstrated as a rate-limiting step in human cellular telomerase activation, and it is suppressed by multiple tumor-suppressor pathways in normal human cells but is activated by numerous oncogenic transcription factors (Meyerson et al, 1997;Liu et al, 2000;Cong et al, 2002;Lin and Elledge, 2003;Goueli and Janknecht, 2004). After its expression, regulations of the subcellular transportation of the TERT protein contribute to telomere homeostasis maintenance in telomerase-positive cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…The activity of the ribonucleoprotein complex telomerase is reliant on the expression of both hTR and hTERT genes, the regulation of which is tightly coordinated on multiple levels by transcriptional, post-transcriptional (Zhao et al, 2000(Zhao et al, , 2005Cong et al, 2002;Anderson et al, 2006;Bilsland et al, 2006) and epigenetic mechanisms (Atkinson et al, 2005;Serakinci et al, 2006). In most normal somatic cells, telomerase is inactivated following development so that telomeres shorten after each round of replication until they reach a critical length, signalling senescence or cell death.…”
mentioning
confidence: 99%
“…Telomerase is not active in quiescent somatic cells but is usually required for cell immortalization and plays an important role in oncogenesis. [1][2][3][4][5][6][7] Using the telomere repeat amplification protocol (TRAP), a PCR-based assay described by Kim et al 8 in 1994 telomerase activity has been demonstrated in over 80% of malignant tumors from various organs. 9 Thus, telomerase activity might play a role as a diagnostic marker of malignancy.…”
mentioning
confidence: 99%